2008
DOI: 10.1089/ast.2007.0196
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Abundant Cellulose Microfibers Encased in 250 Ma Permian Halite: A Macromolecular Target in the Search for Life on Other Planets

Abstract: In this study, we utilized transmission electron microscopy to examine the contents of fluid inclusions in halite (NaCl) and solid halite crystals collected 650 m below the surface from the Late Permian Salado Formation in southeastern New Mexico (USA). The halite has been isolated from contaminating groundwater since deposition approximately 250 Ma ago. We show that abundant cellulose microfibers are present in the halite and appear remarkably intact. The cellulose is in the form of 5 nm microfibers as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
(58 reference statements)
0
23
0
Order By: Relevance
“…For example, intact and abundant cellulose fibres have been recovered from subsurface halite deposits 250 Ma old (Griffith et al 2008). Spore-forming bacteria have been extracted and reactivated from inclusions in the same halite crystals (Vreeland et al 2000;Satterfield et al 2005).…”
Section: (B) Implications For the Search For Biomarkers On Marsmentioning
confidence: 99%
“…For example, intact and abundant cellulose fibres have been recovered from subsurface halite deposits 250 Ma old (Griffith et al 2008). Spore-forming bacteria have been extracted and reactivated from inclusions in the same halite crystals (Vreeland et al 2000;Satterfield et al 2005).…”
Section: (B) Implications For the Search For Biomarkers On Marsmentioning
confidence: 99%
“…Because trees are long-lived and tree fossils are abundant in the fossil record, workers have long sought to gain physiological (Gessler et al, 2009;Offermann et al, 2011) or environmental information from the oxygen isotope composition of both modern (Brienen et al, 2012;Knorre et al, 2010;Loader et al, 2010Loader et al, , 2007McCarroll and Loader, 2004;Poussart et al, 2004;Rinne et al, 2013;Saurer et al, 2008;Treydte et al, 2006;Young et al, 2015) and ancient wood (Jahren and Sternberg, 2002, 2008Richter et al, 2008a;Wolfe et al, 2012). Cellulose has been the substrate of choice because it is resistant to degradation (e.g., Griffith et al, 2008;Jahren and Sternberg, 2002) and can be extracted from heterogeneous lignin complexes (Green, 1963 (Csank et al, 2013;Richter et al, 2008b;Saurer et al, 1997;Sternberg et al, 2007;Waterhouse et al, 2002;Yakir and DeNiro, 1990). Most of this work has been performed using whole leaf tissues or whole tree-rings due to the large amount of plant tissue required for classical isotope analysis (e.g., Sternberg, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Her work has shown that this lake is stratified vertically, horizontally, and temporally. Weaving public outreach into her research, Dr. Baxter turned this unique approach to science into “Great Salt Lake Institute,” which facilitates research and education on this unique body of water (Representative references: Baxter et al, 2005; Griffith et al, 2008; Meuser et al, 2013). …”
Section: Resultsmentioning
confidence: 99%